The salvage therapy utilizing human umbilical cord-derived mesenchymal stem cells for the treatment of critically ill patients with COVID-19 - Weiqi Yao; Weiqi Yao; Weiqi Yao; Boran Li; Yingan Jiang; Qiaoyu Yuan; Qiaoyu Yuan; Wenjie Wu; Wenjie Wu; Ruizhen Hou; Ruizhen Hou; Qi Qi; et al. (Frontiers in Immunology, 2025)
BackgroundThe therapeutic options for patients with coronavirus disease (COVID-19) are limited. Mesenchymal stem cells (MSCs) have immunomodulatory and regenerative properties that may inhibit excessive inflammatory responses, promote recovery from COVID-19-induced lung injury, and potentially serve as a therapeutic option.MethodsAn evaluation of the safety and efficacy of using human umbilical cord mesenchymal stem cells (hUC-MSCs) in 5 critically ill patients with COVID-19 was conducted in this study. In all patients, hUC-MSCs were administered intravenously three times at a dosage of 3 × 107 cells per time, 2 days between each infusion. Safety was evaluated using adverse events. The efficacy was assessed by coagulation function (serum D dimer), inflammatory index (CRP and IL-6) and immune index (lymphocyte count, neutrophil count, CD4, CD19, and CD16 + 56), as well as chest computed tomography (CT) images. Post-infusion visits focused on oxygen saturation and progression of lung lesions.ResultsInfusions of hUC-MSCs were not associated with any serious adverse events. The CT scans indicate that lung lesions have been adequately controlled after receiving the hUC-MSCs. HUC-MSCs injection improved immune system function and alleviated inflammation.ConclusionsAccording to our findings, intravenous infusion of hUC-MSCs has proven to be safe, and it has also proven to show potential therapeutic benefits for patients with severe COVID-19.